Financial Inclusion: A Step Towards Developed Nation (Journal of Finance, Business and Management Studies, 2024)
Financial inclusion is an emerging economic growth paradigm, especially in developing countries like India. It is one of the major factors which has contributed to the growth and development of Indian economy. Financial inclusion refers to the delivery of banking products and services at affordable terms and conditions. Accessibility of financial services at affordable prices has been always a global issue. Therefore, comprehensive financial system is required in our country. In order to enhance GDP and ease of doing business rank, financial inclusion is top objective of our government. In the current scenario financial institutions are the robust pillars of progress of the economy. The objective of this study is to examine the impact of financial inclusion on growth and development of Indian economy. Secondary data has been used in this study. Prime Minister Shri Narendra Modi launched Pradhan Mantri Jan Dhan Yojna on 28th August, 2014. This policy aims at accessing financial services namely banking/saving, deposit accounts, insurance and pension in an affordable manner. Result shows that there has been increase in number of bank branches, outlets and savings accounts from 2014 to 2023 which has significantly contributed to the development of GDP of our economy.
Keywords: Financial inclusion; GDP; Banking sector; Indian economy